Accelerated Fruiting of Sea Buckthorn (Hippophae rhamnoides L.) Meadow-Gardens in Southeast Kazakhstan - Oleichenko, Sergey; Ahmad, Tanveer; Yessenaliyeva, Maira; Aksemser, Taizhan; Tariq, Rana Muhammad Sabir (Journal of Agriculture and Biology, 2025)
This work is novel because it demonstrates that high-density meadow-garden technology enables commercial fruiting of sea buckthorn (Hippophae rhamnoides L.) as early as the second year- a major advancement over traditional systems. The accelerated establishment and productivity of sea buckthorn in meadow-garden systems represent an important direction for enhancing the economic sustainability of fruit production in harsh continental climates. This study assessed the productivity potential of a two year old sea buckthorn meadow garden established under the sharp continental conditions of the Semirechye farm, Almaty region, Kazakhstan. Seven varieties developed by the M.A. Lisavenko Siberian Research Institute of Horticulture were evaluated at a planting density of 40,000 plants/ha. Only two varieties (Augustine and Inia) entered the stage of commercial fruiting by the second year. The variety Augustine demonstrated the highest productivity, yielding 25 t/ha, whereas Inia produced 13 t/ha. In addition to yield, Augustine was characterized by superior fruit size (1.15 g/berry), which was twice that of the control variety Elizaveta and 1.78 times greater than Inia. These results highlight the clear advantage of Augustine for early-fruiting meadow-gardens in Kazakhstan. Economic analysis showed that cultivation of Augustine enables near-complete recovery of investment and operational costs by the second year, despite reliance on labor-intensive manual harvesting. Furthermore, profitability is expected to increase substantially in the third year with the planned application of technological innovations, including complete above-ground cutting of shrubs, shock freezing, and mechanized fruit detachment. The findings highlight Augustine as the most promising cultivar for early commercial returns under Kazakhstan’s sharp continental climate.
Keywords: Sea bucktorn; Meadow garden; Industry; Kazakhstan